How do maternal emotion and sleep conditions affect infant sleep: a prospective cohort study - Xuemei Lin; Ronghui Zhai; Jiafeng Mo; Jingzhou Sun; Peishan Chen; Yuejun Huang (BMC, 2022)
Abstract Background Recent studies suggest that the incidence of infant sleep disorder is related to maternal emotional and sleep conditions, but how they influence each other is not fully understood. Methods A total of 513 pairs of parents and infants were enrolled in this prospective cohort study. Maternal emotional and sleep conditions were assessed using a self-rating depression scale, self-rating anxiety scale, and Pittsburgh Sleep Quality Index at the third trimester and within 3 months after delivery. Infant sleep was assessed by the Brief Screening Questionnaire for Infant Sleep Problems within 3 months after birth. Expression of the glucocorticoid receptor (GR), melatonin receptors (MR), exchange proteins directly activated by cAMP (EPAC) receptors, and dopamine receptor (DR) in the placenta was detected by immunohistochemistry. Methylation of the promoter regions for the GR (NR3C1 and NR3C2), MR (MTNR1A and MTNR1B), EPAC (RASGRF1 and RASGRF2), and DR (DRD1 and DRD2) genes was assessed by next generation sequencing-based bisulfite sequencing PCR. Results The incidence of sleep disorders in infants 0-3 months of age in this cohort was 40.5%. Risk factors for infant sleep disorder were low education level of the father, depression of father, maternal postpartum depression, postpartum anxiety, postpartum sleep disorder, and maternal sleep disorder extend from the third trimester to postpartum. There was no difference in expression of placental DR, GR, MR, and EPAC between mothers whose infants were with and without sleep disorders. Methylation of MTNR1B was higher and expression of MR was lower in the placenta of mothers with sleep disorder in the third trimester than in mothers without sleep disorder. Level of NR3C2 methylation was lower and GR expression was higher in the placenta of mothers with sleep disorder extend from the third trimester to postpartum than in mothers without sleep disorder. Conclusion Maternal sleep disorders in the third trimester could lead to decreased MR expression by up-regulating MTNR1B methylation, and then resulting in elevated cortisol and increased GR expression by down-regulating NR3C2 methylation, which could increase the incidence of maternal postpartum sleep disorders, finally, the maternal postpartum sleep disorder could result in the high incidence of infant sleep disorder.